ショウワキチ シュウヘン ノ コショウスイ ノ モニタリング - 村山, 治太; ムラヤマ, ハルタ; 綿抜, 邦彦; ワタヌキ, クニヒコ; 中谷, 周; ナカヤ, シュウ; 久保田, 秀紀; クボタ, ヒデキ; 鳥居, 鉄也; トリイ, テツヤ; Murayama, Haruta; Watanuki, Kunihiko; et al. (1981)
P(論文) 昭和基地付近の露岩地帯には多数の湖沼が存在し, その溶存塩の濃度も広い範囲にまたがっている。塩化物イオン濃度で溶存塩の多寡を示すと, 最低値1.3mg/l, 最大値210g/l(20℃の密度1.223)である。これら溶存している塩類の供給源はさまざまであり, 夏季には生物活動が盛んな湖沼も多い。これら湖沼の水質が長年月にどのように変動するかは, 地球化学的立場から興味がある。また, これら湖沼に対して昭和基地を中心に活動する人の影響がどのように現れるかを知るために, 環境科学の立場から, 次の5つの湖沼を地球化学的継続観測定点に選び, モニタリングをはじめた;水汲み沢(東オングル島), 大池(西オングル島), ぬるめ池(ラングホブデ), 舟底池(スカルブスネス), スカーレン大池(スカーレン)。これらの池は1)接近・採水がしやすく, 2)基地からの距離が適当であり, 3)複数の人が調査し, 結果が公表されている, などの理由から選ばれた。現在までに知り得た化学成分の組成を表に示す。 Since 1957 with the commencement of the activities of the Japanese Antarctic Research Expedition, geochemical investigations of lakes in the vicinity of Syowa Station have been carried out. There are various kinds of lakes in the chemical composition of water. As to the chloride ion, its concentration ranged from 1.3mg/l to 210g/l. It is one of the interesting problems to pursue the long-term change of chemical composition of water in the various lakes relating to the change of the meteorological conditions. The long-term observation of lake water also contributes to the monitoring of human impacts on the natural environment. Five lakes were selected as the objects for the long-term geochemical observation, which started in the 1978 winter season. The data collected up to 1978 on the five lakes were compiled. departmental bulletin paper